Impact of Pulmonary Arterial Hypertension on Employment, Work Productivity, and Quality of Life - Results of a Cross-Sectional Multi-Center Study - Fuge, Jan; Park, Da-Hee; von Lengerke, Thomas; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein A.; Kamp, Jan C.; Hoeper, Marius M.; Olsson, Karen M. (Frontiers in Psychiatry, 2022)
Introduction Data on burden of pulmonary arterial hypertension (PAH) are mostly limited to physical and clinical endpoints as well as quality of life. Research on employment, work productivity and educational background is scarce. Aim of this study was to assess the impact of PAH on employment status and work productivity in Germany. Material and Methods In a multicenter cross-sectional survey, patients with PAH were surveyed in two large pulmonary hypertension referral centers in Germany. The survey contained questions on education, employment, work productivity (WPAI, also at time of diagnosis), quality of life (QoL) and socioeconomic status. Additional data was assessed using clinical research database for 6-minute walk distance (6MWD), WHO functional class (WHO FC) and N-terminal fragment of pro-brain natriuretic peptide (NT-proBNP). All patients provided written informed consent and the institutional review board approved this study. Results 212 patients were surveyed (72% female, median 57 years) approximately 6 years after initial PAH diagnosis. 76% had an idiopathic PAH (IPAH) followed by hereditary and associated PAH (10% each). Employment at time of diagnosis was 48% (34% full time, 14% part time) with a productivity as measured by WPAI of 6 points and decreased to 29% (21% full time, 8% part time) at the time of the survey (p<0.001 with a WPAI of 2 points, p<0.001). Logistic regression showed education and 6MWD as predictors for employment. Patients in moderate or high educational category had a 3.6- or 5.6-fold chance, respectively, of being employed (p=0.025 and p=0.019), and per 50m increase of 6MWD odds of being employed were 1.2, p=0.042. Conclusion Patients with PAH had a reduced employment rate which was influenced by education and 6MWD. There was a considerable loss of employment over the course of the disease. Employment should be one possible treatment goal in patients with PAH to provide social participation to this patient group.